Collagen membrane: A new concept in surgical management for mucosal defect in oral sub mucous fibrosis - Kumar, Sourav; Nayak, Dipti; Kumar, Shashank; Khan, Musaab; Rastogi, Reshu; Samant, Vaishali (Asian Journal of Medical Sciences, 2021)
Background: Oral submucous fibrosis (OSMF) is a doubtlessly malignant disorder of the oral cavity. The surgical control of this situation involves excision of the fibrotic bands and interpositional grafts to keep the elevated oral opening. Various strategies and graft had been utilized with differing achievement rates. Aims and Objective: Through this study, an attempt was made to evaluate the efficacy of collagen membrane as wound dressing material for mucosal defect in oral submucous fibrosis. Materials and Methods: The study include 30 patients in the age group of 15 to 60 years with stage III or IVa of oral sub mucous fibrosis all of which underwent operation under general anesthesia to enhance their mouth opening by fibrotomy of bands and placement of collagen membrane by same surgeon. After surgery all the patients were accessed under parameter like hemostatic effect, pain relief, granulation tissue formation, epithelization, contracture and reactivity. All patients were given similar prescriptions for pain killer, antibiotics and postoperative instructions. All patients were examined postoperatively. Results: In this study various parameter were accessing the efficacy of collagen membrane on wound defects were recorded. In this 1st parameter hemostatic 28 patients had a score of good (93.3%) with bleeding stopping within 5 minutes after application of membrane and only 2 patients had a score of fair (6.66%). In pain relief analgesics were stopped on the day of 3rd after procedure 16 patients had a good (53.3%) score, 12 patients had a fair (40%) score while only 2 patients gad a poor (6.66%) score. All the patients had sufficient granulation tissue formation of entire wound therefore all the patients had score of good (100%) at the end of two weeks. Epithelization was noted in 28 patients who had score of good (93.3%) after 1 month. Contracture of the wound site at the end of 3 months were noted and rated as good in 20 patients (66.6%) while fair (33.3%) in 10 patients. No reactivity of any form was found in any of the subjects (100%). Conclusion: In our study we noticed that collagen membrane was found to be very effective in all the subjects and it provided us satisfactory results as intraoral wound dressing material.